(untitled) (World Economics and Finance Bulletin, 2022)
The current research aimed to analyze the intellectual and applied impact in each of the life stages of the company in both the accounting conservatism and the economic decisions of investors, by applying to 130 views (company / year) in the Iraqi banks listed in the Iraq Stock Exchange for the period from 2011-2020.